Implementasi Smart System Berbasis Internet of Things (IoT) dalam Meningkatkan Literasi Teknologi Siswa di SMK Negeri 5 Telkom Banda Aceh - Susmanto, Susmanto; Munawir, Munawir; Elvitriana, Elvitriana; Yanti, Yeni; Zulfan, Zulfan; Nurhanif, Nurhanif; Teuku Andiansyah; Nailis Sa’adah; Cut Nanda Nurbadriani; Nizam Albar; Taufik Hidayat; Muhammad Syamsu Rizal; Maulinda, Maulinda; Dewi Mulyati; Safriza Naufal Amzad; Tajus Syabrina; Dini Syahriza Fahlevi; Anas, Anas; Rafif Firdaus; M. Rizki Rayyandi; Nuzul Misra; Kayla Arrosa Diputri (Lembaga Teewan Journal Solutions, 2026)
The rapid development of digital technology requires vocational high school students to possess technological literacy and practical skills aligned with the demands of the modern workplace. This Community Service Program aimed to improve the technological literacy of students at SMK Negeri 5 Telkom Banda Aceh through the implementation of a smart system based on the Internet of Things (IoT). The activity involved 50 students and employed a learning-by-doing approach through pre-implementation, implementation, and evaluation stages. Activities included delivering basic concepts, demonstrating smart systems, assembling components, basic programming, system testing, troubleshooting, and mentoring. Evaluation was conducted through pretests, posttests, skill observations, and practical performance assessments. The results showed that the participants’ average score increased from 75.4 in the pretest to 85.6 in the posttest, representing a 13.53% increase. Furthermore, 75% of participants were able to assemble components, perform basic programming, conduct testing, and explain the operation of a simple smart system. These results demonstrate that hands-on learning can effectively improve students’ technological understanding and practical skills while fostering problem-solving, creativity, and collaboration. Keywords: Internet of Things; smart system; technological literacy; vocational students; learning by doing.